The Implementation of Islamic Moderation Principles in Addressing the Challenges of Political Identity Polarization - Leniawati, Iis; Haq, Mochamad Ziaul (Integritas Terbuka: Peace and Interfaith Studies, 2024)
This article aims to analyze the application of the principles of Islamic moderation (wasatiyyah) in addressing the challenges of identity politics, particularly in mitigating social polarization based on religion and ideology. The study employs a qualitative approach with data collection through literature review. The findings show that the values of Islamic moderation, such as balance, social justice, and compassion, play a significant role in creating inclusive and peaceful politics. The principles of wasatiyyah promote dialogue between groups, prevent identity-based conflicts in Indonesia, and establish fair and harmonious political policies. These findings also confirm that the implementation of Islamic moderation values can strengthen social and political stability in diverse societies. This research contributes to the development of theories and practices in politics based on the values of religious moderation and offers new perspectives for formulating strategies to address political polarization in multicultural societies.